UPAYA MENINGKATKAN MOTIVASI BELAJAR IPA DENGAN METODE PEMBELAJARAN PENEMUAN TERBIMBING - Maftuchah, Umi (WAHANA PEDAGOGIKA, 2016)
Learning the science subject primarily of the first graders at elementary desperately need direction and guidance from the teacher in improving the studentsâ achievement of the first graders at the first state Elementary School in the academic year of 2015 / 2016. So, the students through Guided discovery learning method could improve the academic achievement. The guided discovery Learning had a positive impact in improving the studentsâ achievement marked by the increased of mastery learning students in each cycles, the first cycle (50%) with an average value of 65.5, the second cycle (100%) with the average value of 93.10. The application of guided discovery learning method had a positive effect, which could increase the students motivation shown by the average response of students stating that the students were interested in and fond of guided discovery learning method so that they became motivated to learn.